Hematological constants in women living at high altitudes - Berendsohn, Siegfried (1957)
Were conducted to determine the constants hemóticas 55 women living in high altitudes (4,540 Morococha mts. Above the sea), apparently healthy, and the results obtained were subjected to statistical analysis and compared with similar studies have been carried out to sea level.